Peran Strategis Umat Islam Indonesia: Refleksi dari Sudut Pandang Partisipan tentang Reformasi, Politisasi Agama, dan Sekularisasi - Manan, Nuraini A. (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research examines the strategic role of Muslims in Indonesia in the context of reform, religious politicization and secularization. With a participatory approach, this study explores participants' views on these three main issues and their impact on social and political life in Indonesia. This research finds that reform in Indonesia must rely on Islamic principles which emphasize continuous evolution and maintaining good traditions while adopting new and better things. The politicization of religion is identified as a crucial problem that threatens the sacredness of religion, resulting in desacralization and potential social conflict. On the other hand, misunderstood secularization can also pose challenges to the integration of religious values ​​in everyday life. This study concludes that a balance between religious values ​​and modern developments is very important for the progress of Muslims and the Indonesian nation as a whole.